2011
DOI: 10.1016/j.neurobiolaging.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic players in multiple system atrophy: unfolding the nature of the beast

Abstract: Multiple system atrophy (MSA) is a fatal oligodendrogliopathy characterized by prominent α-synuclein inclusions resulting in a neuronal multisystem degeneration. Until recently MSA was widely conceived as a nongenetic disorder. However, during the last years a few postmortem verified Mendelian pedigrees have been reported consistent with monogenic disease in rare cases of MSA. Further, within the last 2 decades several genes have been associated with an increased risk of MSA, first and foremost the SNCA gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 101 publications
2
38
0
Order By: Relevance
“…Genetic research into MSA has so far been lagging behind that of related neurodegenerative diseases, such as PD, but recent studies suggest that genetic factors have a role in this disease [329]. To date the majority of genetic studies in MSA have screened candidate genes for coding mutations, including SNCA, MAPT, and other PD genes, but more recently, some association studies screening for common genetic variants in MSA have been reported, and a GWAS is currently in progress (see [330].…”
Section: It Improves Mitochondrial Dysfunction Altersmentioning
confidence: 99%
“…Genetic research into MSA has so far been lagging behind that of related neurodegenerative diseases, such as PD, but recent studies suggest that genetic factors have a role in this disease [329]. To date the majority of genetic studies in MSA have screened candidate genes for coding mutations, including SNCA, MAPT, and other PD genes, but more recently, some association studies screening for common genetic variants in MSA have been reported, and a GWAS is currently in progress (see [330].…”
Section: It Improves Mitochondrial Dysfunction Altersmentioning
confidence: 99%
“…When MSA is in the differential diagnosis, genetic testing for the spinocerebellar ataxias in such patients is recommended to essentially rule out a familial ataxia. [25, 26]…”
Section: Clinical and Neuropathological Features Of Msamentioning
confidence: 99%
“…[1, 26] Despite this well-defined classification system of MSA, current treatment options for patients with either subtype is far from optimal: not only is there no treatment to delay the progression of disease, but levodopa is considered the primary treatment for symptoms, which has a “modest and non-sustained effect.”[28, 29] While approximately 30% of MSA patients demonstrate an initial response to levodopa therapy, this response does not persist although patients often find it hard to stop this drug. [30]…”
Section: Clinical and Neuropathological Features Of Msamentioning
confidence: 99%
See 2 more Smart Citations